2003
DOI: 10.2307/4004038
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxic Plant Estimation in Grazing Sheep Ingesta and Feces

Abstract: Romerillo' (Baccharis coridifolia DC), 'duraznillo negro' (Cestrum parqui L'Herit.), and `sunchillo' (Wedelia glauca (Ort.) Hoff.) are highly toxic species producing important economic losses of livestock in Argentina. This study assessed the accuracy and precision in the estimation of the percentage and the mass of these species in the ingesta and feces of sheep experimentally poisoned. This study also evaluated whether the quantified percentage and the calculated mass of each toxic species in the rumen+retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…However, the percentage of recognizable fragments after digestion in this species is low (30%), and lower than that determined for other acute toxic species that also grow in the Buenos Aires province, such as duraznillo negro (73%) and sunchillo (51%) (Cid et al 2003), although the three of them had similar DM percentage (from 18% to 20%). The epidermis is covered by indigestible cutine that inhibits digestion, protecting cell walls of microbe attacks.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, the percentage of recognizable fragments after digestion in this species is low (30%), and lower than that determined for other acute toxic species that also grow in the Buenos Aires province, such as duraznillo negro (73%) and sunchillo (51%) (Cid et al 2003), although the three of them had similar DM percentage (from 18% to 20%). The epidermis is covered by indigestible cutine that inhibits digestion, protecting cell walls of microbe attacks.…”
Section: Discussionmentioning
confidence: 86%
“…These percentages are lower than those found in other experiments of forced intoxication done with other acute toxic species. Cid et al (2003) reported recovers of 96.5, 92.2 and 92.0% of the amount supplied for duraznillo negro, romerillo and sunchillo, respectively. A low recovery of a toxic species fragments in the digesta of a dead animal could be related to their high degradation by digestion, or to their lost in the feces produced from intake to dead.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations